The physical and optical properties of AZO thin films on teflon substrate at low deposition temperature by spray pyrolysis - Sofea Nabila Hazmin; F. S. S. Zahid; N. S. M. Sauki; M. H. Mamat; M. N. Amalina (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents the physical and optical properties of AZO thin films on Teflon substrate at low deposition temperature by spray pyrolysis. In this study, the effect of different process parameters such as spray time and substrate to nozzle distance on the physical and optical characteristic of aluminium doped zinc oxide (AZO) deposited on Teflon substrates was investigated. The AZO thin films were successfully deposited onto Teflon substrate by spray pyrolysis technique at low deposition temperature. The physical analysis by X-ray diffraction (XRD) shows that the deposited Teflon substrate films have a preferred orientation along the direction (100) and (101). Optical measurements were conducted using Jasco/V-670 Ex Uv-Vis-NIR Spectrophotometer model to confirms that in visible ray it is possible to get good reflectance of AZO films with a reflection of 80%. The values of band gaps Eg were calculated from the spectra of UV-Visible reflectance that were vary between 3.06 and 3.14 eV.